The Relationship Between Culture and the Modifiable Risk Factors of Dementia Among Indigenous Peoples in Canada, the USA, Australia, and New Zealand: A Scoping Review Protocol - Brittany Skov; Angela M. Ashley; Ishaq Malik; Hannah Storrs; Elaine Toombs; Christopher J. Mushquash (International Journal of Qualitative Methods)
Background: Compared to non-Indigenous peoples, the prevalence of dementia is higher among Indigenous Peoples in Canada, the United States, New Zealand, and Australia, and poses significant challenges to individual, family, and community health and well-being. Connection to culture, a social determinant of health for Indigenous Peoples, may influence the prevalence and incidence of modifiable risk factors for dementia (e.g., excessive alcohol use and diabetes). However, no existing scoping reviews have summarized the available literature regarding connection to culture and modifiable risk factors for dementia among Indigenous Peoples in Canada, the United States, New Zealand, and Australia. We will conduct a scoping review to identify, summarize, and evaluate the literature in this area, while also highlighting gender-based differences. Methods: We will use the 2020 Joanna Briggs Institute methodology for scoping reviews. We will systematically search PsychInfo, Web of Science, PubMed, ERIC, CINAHL, and gray literature databases to identify relevant qualitative and quantitative studies. Four reviewers will assess titles, abstracts, and full-text articles for inclusion. We will chart and synthesize extracted data to summarize the influence of connection to culture on modifiable risk factors of dementia and assess whether gender impacts this relationship. We will also evaluate the methodological quality of published literature using the Consolidated Criteria for Strengthening Reporting of Health Research involving Indigenous peoples. Reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guidelines. Discussion: This review will synthesize and provide important insight into the relationship between connection to Indigenous culture and modifiable risk factors for dementia. Findings may help to inform Indigenous health promotion initiatives, policy, future research, and clinical practice. Scoping Review Registration: Open Science Framework ( https://osf.io/3ykdr ).